دراسة ظاهرة صدأ حديد التسليح في المنشآت الخرسانية المسلحة في مدن الساحل السوري - مشكلة وحلول - تريكية, علي (Latakia University Journal -Engineering Sciences Series, 2019)
Corrosion of reinforcing steel in reinforced concrete structures on the Syrian coast is a serious problem that requires extensive attention and research due to the increase in chloride salts in the adjacent soil and the saturation of atmospheric humidity in the coastal area with chlorides. The high temperatures in summer and low in winter encourage the contraction of both plastic and dry, and that the cracks facilitate the penetration of harmful ions in the soil, water and atmosphere surrounding the facilities causing rupture of the protective layer surrounding the rebar and the occurrence of rust phenomenon with cracking and fragmentation of the concrete cover surrounding the rebar. In addition, there may be structural damage in the members of reinforced concrete due to loss of adhesion between the iron and concrete and corrosion of the rebar section and in some cases the damage extends to structural failure. This research aims to study the phenomenon of rust in armed concrete installations in the Syrian coast and to know their causes and effects and to know the forms of defects suffered and know the factors to control them. Armed forces that suffer from the deterioration of the concrete in the structural elements, through which they were inspected on these structures, and identify the forms of defects and cracks in them, in addition to know the causes, and conduct a series of tests, and analysis of the results as assessed Develop the necessary scientific recommendations to reduce or prevent the occurrence of such defects in the future. The results of the analysis and evaluation of the studied cases showed the need to adjust the design and implementation specifications given by the Syrian Arab code, which should be followed in accordance with the international codes to avoid the corrosion of reinforcing steel in reinforced concrete. يُعد تآكل حديد التسليح في المنشآت الخرسانية المسلحة في الساحل السوري من المشاكل الخطيرة التي تحتاج إلى عناية وبحوث موسعة نظراً لزيادة نسبة أملاح الكلوريدات في التربة المجاورة للشاطئ وتشبع رطوبة الجو في المنطقة الساحلية بالكلوريدات. كما أن ارتفاع درجات الحرارة صيفاً وانخفاضها شتاءً يشجع على حدوث الانكماش بنوعيه اللدن والجاف، وإن حصول التشققات يُسهل اختراق الأيونات الضارة المتواجدة في التربة والمياه والجو المحيط بالعناصر الإنشائية مسبباً تكسر طبقة الحماية المحيطة بحديد التسليح وحصول ظاهرة الصدأ مع تشقق وتشظي الغطاء الخرساني المحيط بحديد التسليح إضافة إلى ذلك قد يحصل ضرر إنشائي في أعضاء الخرسانة المسلحة بسبب فقدان التلاصق بين الحديد والخرسانة وتآكل مقطع حديد التسليح وفي بعض الحالات يمتد الضرر إلى فشل إنشائي. يهدف هذا البحث إلى دراسة ظاهرة الصدأ في المنشآت الخرسانية المسلحة في الساحل السوري ومعرفة أسبابها وتأثيراتها ومعرفة أشكال العيوب التي تعاني منها وعوامل السيطرة عليها ، ولتحقيق هدفنا قمنا برصد معطيات الكودات ومواصفات التصميم لتفادي الصدأ في المنشآت الخرسانية المسلحة , وإجراء دراسة ميدانية للعديد من المنشآت الخرسانية المسلحة التي تعاني من تدهور البيتون المسلح في عناصرها الإنشائية , تم من خلالها الكشف على تلك المنشآت, وتحديد أشكال العيوب والتصدعات فيها, بالإضافة إلى معرفة أسبابها, وإجراء مجموعة من الاختبارات, وتحليل نتائجها كما قمنا بوضع التوصيات العلمية اللازمة للإقلال أو منع حدوث مثل هذه العيوب مستقبلاً . بينت نتائج التحليل والتقييم للحالات المدروسة ضرورة التقيد بمواصفات التصميم والتنفيذ التي يعطيها الكود العربي السوري التي يلزم اتباعها وفق ما تنص عليه الكودات العالمية لتفادي صدأ حديد التسليح في الخرسانة المسلحة.